Evaluation of a Flexible NOTA-RGD Kit Solution Using Gallium-68 from Different 68Ge/68Ga-Generators: Pharmacokinetics and Biodistribution in Nonhuman Primates and Demonstration of Solitary Pulmonary Nodule Imaging in Humans. - Ebenhan, Thomas; Schoeman, Isabel; Rossouw, Daniel; Grobler, Anne; Marjanovic-Painter, Biljana; Wagener, Judith; Kruger, Hendrik; Sathekge, Mike; Zeevaart, Jan; Rossouw, Daniel D; Kruger, Hendrik G; Sathekge, Mike M; et al. (Molecular Imaging & Biology, 2017)
Purpose: Radiopharmaceuticals containing the motive tripeptide arginyl-glycyl-asparatic acid (RGD) are known to target ανβ3 integrins during tumor angiogenesis. A more generic kit radiolabeling procedure accommodating Ga-68 from different generators was developed for NOTA-RGD and evaluated for its versatile use and safety in subsequent in vivo applications. The [68Ga]NOTA-RGD kit was further verified for its expected biodistribution and pharmacokinetics in nonhuman primates and its clinical sensitivity to detect solitary pulmonary nodules (SPN) in cancer patients.Procedures: Single vial kits containing 28-56 nmol of NOTA-cyclo-Arg-Gly-Asp-d-Tyr-Lys (NOTA-RGD) and sodium acetate trihydrate buffer were formulated. Versatility of the NOTA-RGD radiolabeling performance and adaption to a TiO2- and a SnO2-based generator type, characterization and long-term storage stability of the kits were carried out. The blood clearance and urine recovery kinetics as well as the image-guided biodistribution of [68Ga]NOTA-RGD was studied in a vervet monkey model. [68Ga]NOTA-RGD kits were further tested clinically to target solitary pulmonary nodules.Results: The kits could be successfully formulated warranting integrity over 3-4 months with a good [68Ga]NOTA-RGD radiolabeling performance (radiochemical purity >95 %, decay corrected yield 76-94 %, specific activity of 8.8-37.9 GBq/μmol) The kits met all quality requirements to be further tested in vivo. [68Ga]NOTA-RGD cleared rapidly from blood and was majorly excreted via the renal route. The liver, spleen, heart and intestines showed initial uptake with steadily declining tissue activity concentration over time. In addition, the [68Ga]NOTA-RGD kit allowed for delineation of SPN from non-malignant lung tissue in humans.Conclusions: A more versatile radiolabeling procedure using kit-formulated NOTA-RGD and different generator types was achieved. The uncompromised in vivo behavior and efficient targeting of SPN warrants further investigations on the clinical relevance of [68Ga]NOTA-RGD derivatives to implement initial guidelines and management of patients, with regard to integrin targeted imaging.